The Effect of Education and Training on Improving the Quality of Employee Work at PPA MDC Medan - Rihartd Bronson Daulat Siahaan (Institute of Computer Science (IOCS), 2019)
Education is something that must be done by an organization or institution in developing its human resources in supporting the implementation of good training in improving work understanding for each employee. The training is a learning phase which is used to give understanding to every worker in understanding the good work system in the organization. Training is very important to develop an understanding of each HR. The quality of work is the result to be obtained from the performance results of each HR. In this case education and training are ways of developing human resources in aligning the growth of the human resources of an organization. The research objectives are to: 1) Determine the effect of education on improving the work quality of Medan MDC PPA employees, 2) Know the effect of training on improving the work quality of Medan MDC PPA employees and determine the effect of education and training on improving the work quality of Medan MDC PPA employees by sampling techniques in total sampling so the number of samples was 62 people Research conclusions are: Education has a significant effect on improving the quality of work of employees and is a dominant variable influencing the improvement of the quality of work of PPA MDC Medan employees, Training has a significant effect on improving the quality of work of PPA MDC Medan employees, education and training simultaneously have a significant effect on improving the quality of employee work PPA MDC Medan, Adjusted R Square value of 0.725 or 72.50%, meaning that the research variables in the form of Research and Training contribute or explain in improving the work quality of employees of PPA MDC Medan by 72.50% while the remaining 27.50% is influenced by other factors beyond research.